Social media como estrategia de comunicación para el posicionamiento de la empresa HANGAR 29 en el segmento de 16 a 35 años del distrito de Trujillo. - Castro Dionicio, José Agapito (2012)
This research work was developed with the aim of developing a Communications Strategy based on Social Media for precise positioning of the company HANGAR29 on the segment from 16 to 35 years in the District of Trujillo linked to a highly competitive environment . The research question is: What communication strategy allows the positioning of the company HANGAR29 in the market segment of 16 to 35 years in the District ofTrujillo? , Which assumption is the communication strategy based on SOCIALMEDIA allows the positioning of the company HANGAR29 segment aged 16 to 35 years of age in the district of Trujillo, defined as an independent variable basedCommunication Strategy and Social Media dependent variable positioning of the company HANGAR29. The study population was made up of the target audiencethe company is directed HANGAR29 (District youth Trujillo, Department of Libertad of between 16 to 35 years old), who have access to social networks that is 125,260people . From which, we defined the sample of 383 people by the method of probability sampling. For the present research report was used quasi-experimental design, and the following methods: deductive-inductive method, analytic-synthetic and statistician, and finally applied the following research techniques: interviews, surveys, monitoringweb with Social Mention, Web Traffic, Value of Construction Post Web. Among the most relevant results of the study is the lack of brand identity as appliedto administrative interviews of small business and brand recognition by business users HANGAR 29.